Postoperative biliary anastomotic strictures after pancreaticoduodenectomy. Issue 11 (November 2021) - Javed, Ammar A.; Mirza, Muhammad B.; Sham, Jonathan G.; Ali, Daniyal M.; Jones, George F.; Sanjeevi, Srinivas; Burkhart, Richard A.; Cameron, John L.; Weiss, Matthew J.; Wolfgang, Christopher L.; He, Jin
Abstract: Background: Biliary anastomotic stricture (BAS) is an uncommon complication of pancreaticoduodenectomy (PD). As PDs are performed more frequently, BAS may become a more common pathologic entity requiring clinical engagement. The aim of this study was to report the incidence of BAS in the modern era of pancreatic surgery and identify risk factors associated with it. Methods: Patients undergoing PD at the Johns Hopkins Hospital between 2007 and 2016 were identified using an institutional registry and clinicopathological features were analyzed to identify risk factors associated with BAS. Results: Of 2125 patients identified, 103 (4.9%) developed BAS. Factors independently associated with BAS included laparoscopic approach (HR:2.83, 95%CI:1.35–5.92, p = 0.006), postoperative pancreatic fistula (HR:2.45, 95%CI:1.56–4.16, p < 0.001), postoperative bile leak (BL) (HR:5.26, 95%CI:2.45–11.28, p < 0.001), and administration of adjuvant radiation therapy (HR:6.01, 95%CI:3.19–11.34, p < 0.001). Malignant pathology was associated with lower rates of BAS (HR:0.52, 95%CI:0.30–0.92, p = 0.025). BL was associated with higher rates of early-BAS (HR:16.49, 95%CI:3.28–82.94, p = 0.001) while use of Vicryl suture for biliary enteric anastomosis was associated with lower rates of early-BAS (HR:0.20, 95%CI:0.05–0.93, p = 0.041). Conclusion: Approximately 5% of patients undergoing PD experience BAS. Multiple factors are associated with the development and timing of BAS.